A Review on Perturb and Observe Maximum Power Point Tracking in Photovoltaic System - Rozana Alik; Awang Jusoh; Tole Sutikno (Universitas Ahmad Dahlan, 2015)
Solar energy is becoming popular and has drawn lots of attention from researchers nowadays. However, the output power of the photovoltaic (PV) arrays varies with solar irradiation and temperature, which affect the efficiency of PV arrays. Therefore, Maximum Power Point Tracking (MPPT) control technique is used to extract the maximum available power from the PV arrays. Perturb and Observe (P&O) algorithm is one of the favorite techniques frequently used due to its simplicity and low cost. Yet, the conventional P&O algorithm has several drawbacks, which leads to power loss and lack of efficiency. This paper presents comparison of the basic P&O algorithm with the modified P&O algorithm used for partial shading condition in terms of complexity, accuracy, cost, and basic concept of each method.